Forest Condition in Europe: 2013 technical report of ICP Forests. Report under the UNECE Convention on Long-Range Transboundary Air Pollution (CLRTAP) - Alexa Michel; Walter Seidling; Martin Lorenz; Georg Becher (Johann Heinrich von Thünen-Institut, 2014)
Of the 42 countries that have participated in ICP Forests since 1986, 27 countries reported largescale monitoring data from Level I plots and more detailed forest ecosystem related monitoring data from Level II plots for the year 2012. In total, the participating countries provided information on more than 15,000 plots and more than 220,000 trees. Data analyses for this 2013 Technical Report focused on the impact of air pollution on tree crown condition and on sulphate and nitrogen deposition to forests. In addition, the impact on individual trees of factors other than air pollution, e.g., biotic agents, was assessed. Crown condition is the most widely applied indicator for forest health and vitality of European forests. One of its primary parameters is the rate of defoliation, which is assessed as the percentage of needle/leaf loss in the crown compared to a reference tree with full foliage. The mean defoliation of 114,361 sample trees on 6,168 transnational Level I plots in 2012 was 19.7%. Of all trees assessed in 2012 every fourth to fifth tree (22.9%) was scored as damaged, i.e., had a defoliation rate of more than 25%. In general, broadleaved trees showed a higher mean defoliation rate than conifer species (23.6% and 20.2%, respectively). Oak species still seem to be the most vulnerable of all the investigated species. Of the main species groups, deciduous temperate oak species had the highest mean defoliation (26.5%), closely followed by Mediterranean evergreen oak species (25.2%), and deciduous (sub-) temperate oak species (24.6%). A mean defoliation rate of 19.6% was assessed for European beech (Fagus sylvatica). Coniferous species expressed lower defoliation rates on average, with European spruce (Picea abies) reaching 19.2%, followed by Scots pine (Pinus sylvestris) with 19.3%, and Mediterranean lowland pine species with 20.7%. These figures are, however, not directly comparable to those of previous reports because of fluctuations in the plot sample that are primarily due to changes in the annual participation of countries. Therefore, the temporal development of crown condition was calculated separately from the monitoring results for those countries which have submitted data every year without interruption since 1993, 1998, and 2002, respectively. In addition, maps were drawn that depict temporal species trends in defoliation. The presented results suggest that there was no overall improvement of crown condition for the longest analyzed time period from 1993 to 2012. Over the last 20 years the percentage of plots with clearly increasing mean defoliation (17.2%) even exceeded the share of plots with decreasing defoliation (12.5%) but most of the investigated plots showed no statistically significant change in crown condition (70.3%). Compared to the previous year only, the investigated trees showed on average similar rates of defoliation in 2012. More than three out of four plots (78.7%) showed no statistically significant difference in mean defoliation between those two years. Defoliation increased on 13.8% and decreased on only 7.5% of the plots.
urn:nbn:de:gbv:253-201403-dn053404-7
Keywords: 630